2018
DOI: 10.1002/cia2.12032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platinum and palladium nanocolloid on macrophage polarization in relevance to repigmentation of vitiligo

Abstract: Background Elevated oxidative stress is accepted to be the initial event in vitiligo leading to the final pathological regulation of immune systems known as autoimmune reaction, which destroys melanin‐forming cells, melanocytes. Recently, we reported an efficient topical use of PAPLAL, nanocolloid of platinum and palladium, having intense catalase‐like activity to vitiligo patients. In addition, we found that PAPLAL has dual effects on the AhR and Nrf‐2 pathways in keratinocytes, and suggested its contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Observing the effects of PAPLAL, a nanocolloid of platinum (Pt) and palladium (Pd) that acts in the antioxidant pathway, it was suggested that it regulates the plasticity of Mϕ, inhibiting M1-like polarization and favoring the balance of M2-like populations in the skin. Thus, it decreases the cytotoxic activity at the lesion site and favors the repigmentation and recovery of healthy skin [185]. Another potential treatment option for vitiligo consists of drugs such as aspirin, which inhibit the pro-inflammatory pathways and have already been seen to increase the survival of melanocytes.…”
Section: Vitiligomentioning
confidence: 99%
“…Observing the effects of PAPLAL, a nanocolloid of platinum (Pt) and palladium (Pd) that acts in the antioxidant pathway, it was suggested that it regulates the plasticity of Mϕ, inhibiting M1-like polarization and favoring the balance of M2-like populations in the skin. Thus, it decreases the cytotoxic activity at the lesion site and favors the repigmentation and recovery of healthy skin [185]. Another potential treatment option for vitiligo consists of drugs such as aspirin, which inhibit the pro-inflammatory pathways and have already been seen to increase the survival of melanocytes.…”
Section: Vitiligomentioning
confidence: 99%
“…Different variants of DNA photolyase immobilization on various nanostructured carriers for targeted delivery and stability of the molecule are also considered [ 68 ]. In addition, for example, palladium/platinum nanoparticles themselves can be used to eliminate the effects of photodamage and oxidative stress in cells [ 69 , 70 , 71 ].…”
Section: Dna Photolyases As a Tool Of Protection Against Photodamage Of Human Skin And Its Treatmentmentioning
confidence: 99%